Patient engagement in the development of CF-CBT: A cystic fibrosis-specific cognitive-behavioral intervention for adults - Friedman, Deborah; Kaskas, Maysa M.; Quittner, Alexandra L.; Smith, Beth A.; Georgiopoulos, Anna M. (Frontiers in Psychology, 2022)
Individuals with cystic fibrosis (CF) are at high risk for depression and anxiety, with negative consequences for health and quality of life. Cystic Fibrosis Foundation/European Cystic Fibrosis Society guidelines recommend routine screening, treatment, and preventative efforts. Cognitive-behavioral therapy (CBT) has a large evidence-base for depression/anxiety prevention and treatment. However, traditional CBT protocols require adaptation to address the emotional challenges of coping with CF, stressors related to disease management, and barriers to access to care. The goal of this study was to partner with the CF community to develop an innovative CBT-based intervention for the prevention and treatment of depression and anxiety tailored to CF-specific needs. In-depth feedback was collected via audio-recorded telephone interviews with 16 adults with CF from 3 U.S. CF centers, with purposive sampling across gender, age, ethnicity, and disease severity. A semi-structured interview guide elicited discussion of patient experiences of coping with CF, and perspectives on the acceptability of the content, structure, and delivery model of the proposed intervention. Qualitative analysis utilized a content analytic approach. Participants ranged from 21 to 53 years (M = 35); eight were female; three were Hispanic. Patient-reported most recent FEV1, a measure of lung function based on forced expiratory volume in in one second, ranged from 25 to 113% predicted (M = 72). One participant was post-double lung transplant. Qualitative interviews were analyzed thematically revealing core themes related to the experience of coping with CF. The most frequently cited CF-related stressors were Treatment Burden, Illness Uncertainty, and Financial/Insurance Stress. Participants talked about the interaction of physical symptoms and emotional distress in their daily lives, a topic not typically discussed in routine CF care. Resilience was also a major theme with participants describing strategies they use to cope with CF and hospitalizations. Description of patients’ experiences was incorporated into the program’s intervention manual and patient workbook. Participants also provided direct feedback on the proposed program. Feedback was largely positive regarding program content and structure, suggesting the acceptability of a CF-specific CBT-based intervention for adults with CF. Features to increase accessibility of care including telehealth, inpatient delivery, and team-based care were perceived as advantageous, and participants emphasized the value of a CF-specific mental health intervention. Qualitative findings directly informed the development of CF-CBT, a cognitive-behavioral skills-based program to promote emotional well-being for adults with CF.